Development and Validation of an Abbreviated Version of the Expanded Prostate Cancer Index Composite Instrument for Measuring Health-related Quality of Life Among Prostate Cancer Survivors - Szymanski, Konrad M.; Wei, John T.; Dunn, Rodney L.; Sanda, Martin G. (Urology (Ridgewood, N.J.), 2010)
Widespread implementation of health-related quality-of-life (HRQOL) measurement in prostate cancer practice and research requires concise instruments. With 50 questions, the full-length Expanded Prostate Cancer Index Composite (EPIC) is cumbersome to administer outside of studies focusing exclusively on HRQOL. To facilitate HRQOL measurement in a broad range of prostate cancer research and practice settings, we developed and validated an abbreviated version of the EPIC. The 50 questions that constitute the full-length EPIC-50 were evaluated to identify the items suitable for elimination while retaining the ability to measure the 5 prostate cancer-specific HRQOL domains of the EPIC-50. The resulting abbreviated version (EPIC-26) was validated using question responses from 252 subjects who had undergone brachytherapy, external beam radiotherapy, or prostatectomy for prostate cancer. The EPIC-26 internal consistency was measured by Cronbach's α coefficient and reliability using test–retest correlation. Using the high item–scale correlations, clinically relevant content, and preservation of domain psychometrics, 26 items were retained in the EPIC-26 from the 50 questions in the full-length EPIC-50. A high correlation was observed between the EPIC-50 and EPIC-26 versions for the urinary incontinence, urinary irritation/obstruction, bowel, sexual, and vitality/hormonal domain scores (all r ≥0.96). The correlations between the different domains were low, confirming that EPIC-26 retained the ability to discern the 5 distinct HRQOL domains. The internal consistency and test–retest reliability for EPIC-26 (Cronbach's α ≥0.70 and r ≥0.69, respectively for all 5 HRQOL domains) supported its validity. EPIC-26 is a brief, valid, and reliable subjective measure of health quality among patients with prostate cancer and is suitable for measuring the HRQOL among patients undergoing treatment of early-stage prostate cancer.